Roadside phytocoenoses under conditions of erosion and soil pollution with salt components of deicing reagents - Shavalda, Yauheni; Sudnik, Aliaksandr; Komar, Artur; Batian, Anatoly (Journal of the Belarusian State University. Ecology, 2024)
Roadside phytocenoses along the right-of-way of highways in Minsk and the Minsk region were identified. The identified syntaxa belong to the classes Polygono-Poetea annuae, Artemisietea vulgaris and Molinio-Arrhenatheretea, reflecting the different intensity of a complex of anthropogenic factors on the structure of plant communities in the right-of-way. An assessment was made of the degree of erosion of roadside soils and their salinization as a result of the use of deicing agents and depending on the design of the right-of-way. The «notch» and «embankment» exposures are subject to the greatest erosion, and the maximum area of soil degradation is observed in areas directly next to the road surface of all exposures and on the «notch» slopes. There are signs of migration of Na+ and Cl– ions between soil horizons of 0-10 cm and 10-20 cm within the right-of-way during the growing season – the content of ions in the spring was higher in the upper horizon (0-10 cm); in summer, ion indices were minimally higher in the lower horizon (10-20 cm), being similar in values to the upper horizon. intensity of salt exposure relative to the assumed «toxicity threshold» showed the greatest effect of salinity in the «embankment»; in the «zero position» the effect of salinity was the least. The information obtained on the structure of phytocenoses and their growing conditions made it possible to develop brief recommendations for caring for the right-of-way and creating a sustainable roadside lawn.
Keywords: highway; right-of-way; roadside vegetation; soil erosion; de-icing reagents; anthropogenic salinization; chlorides; water-soluble sodium